State Map, New South Wales: State & Suburban (Australia Universal Publishers Pty Ltd., 2011)
24-hour fuel, National parks, camping, restaurants - points of interest . Hema Maps
Title from panel. . 1 map : color ; 68 x 98 cm, folded to 25 x 15 cm . Hema Maps (Firm) UBD
Includes index and distance table.Indexed list to National Parks, list to information centres, color illustrations, and indexed maps of Canberra CBD and Sydney CBD on verso.
Maps on verso: Sydnet Region -- Sydney throughroads -- Blue Mountains National Park -- Katoomba to Wentworth Falls.
Keywords: History, Geography and Archaeology (3GdJGQjN hGdLZQGajG hGdBKGQs; Roads -- Australia -- New South Wales -- Maps